EXPLORING THE IMPACT OF ARTIFICIAL INTELLIGENCE ON PERSONALIZED ENGLISH LANGUAGE LEARNING ACROSS DIFFERENT PROFICIENCY LEVELS - Qodirqulova Maftunaxon Muhiddin qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Personalized learning within ESL and EFL contexts is increasingly powered by artificial intelligence. This study investigates how AI-enhanced tools influence English language acquisition across varying proficiency levels—beginner, intermediate, and advanced. Participants engaged with adaptive dashboards offering real-time feedback on grammar, vocabulary, pronunciation, and reading comprehension over a twelve-week period. Engagement analytics, language performance measures, learner interviews, and motivational reflections were gathered and examined. Findings suggest that AI personalization significantly boosts linguistic competence and vocabulary retention, especially among beginners. Intermediate learners show notable improvement in grammatical precision and fluency building, while advanced learners benefit from nuanced polishing of complex expressions. Learner motivation rises across all levels, though advanced learners report mixed feelings about AI feedback on subtle language choices. Ethical concerns around data privacy and over-reliance on automated corrections also emerged. Implications for integrating AI tools thoughtfully into language programs are discussed. Educators, instructional designers, and EdTech developers can leverage these findings to better tailor AI-supported learning experiences.